INDEKS GLIKEMIK (IG) DAN RESPONS GLUKOSA POST-PRANDIAL BERAS BERWARNA DARI INDONESIA PADA INDIVIDU SEHAT - Mira Mutiyani; Mona Fitria; Roya Suffah Zain; Indra Wibowo (Poltekkes Kemenkes Bandung, 2020)
Some rice cultivars have been traditionally grown in Indonesia, but only limited researches have been done related on that area. Diabetes is a chronic metabolic illness characterized by hyperglycemia, mainly affected by staple diet pattern as consumption of rice. On the contrary, some traditional pigmented rice varieties are proven to be beneficial in managing different metabolic disorders as diabetes and other metabolic syndrome. Glycemic potential of pigmented rice cultivars namely white rice, red rice, brown rice, and black rice were studied. Brown rice recorded low GI of 51.09 whereas white rice elicited high GI of 72.84, red rice recorded high GI of 70.17, and black rice elicited high GI of 83.83. Hence, brown rice with low GI can be potential as a source of functional food and could play an important role in the management and prevention of diabetes and metabolism disorders